UPAYA DINAS PERHUBUNGAN KOTA PEKANBARU DALAM PENANGGULANGAN MASALAH PUNGUTAN PARKIR LIAR (STUDI KASUS KECAMATAN SUKAJADI KOTA PEKANBARU) - Astina, Nurhaliza astina; Neri Widya Ramailis, (Sisi Lain Realita, 2024)
This research aims to understand the landscape of illegal parking fees in Sukajadi Sub-district, Pekanbaru City, and to examine the efforts of the Pekanbaru City Transportation Department in addressing the issue of illegal parking fees in Sukajadi Sub-district, Pekanbaru City. The research was conducted using qualitative methods, with data collection techniques including interviews and document studies. The efforts of the Transportation Department have shown positive steps, but still require enhancement and innovation to overcome existing challenges. Cooperation between the government, community, and other relevant stakeholders, as well as an approach that considers socio-economic aspects, is key to addressing this issue effectively and sustainably. Although the Pekanbaru City Transportation Department has demonstrated commitment in handling the illegal parking problem, this issue still requires more intensive and integrated management. Close collaboration between the government, community, and other relevant parties is crucial in achieving effective and sustainable Solutions